Institutional change in realizing the value of ecological products: dynamic evolution and local practice based on concept movement theory - Yang, Mingjie; Zhang, Xiaodong; Guo, Rui; Li, Yaolong; Zhong, Fanglei (Frontiers in Environmental Economics, 2025)
The mechanism for realizing the value of ecological products is a critical issue bridging the global Sustainable Development Goals (SDGs) and China's ecological civilization construction. Addressing a key methodological gap between the international TEEB framework (based on natural capital accounting and marginal utility pricing) and China's Gross Ecosystem Product (GEP) accounting, this study employs concept movement theory to deconstruct the dynamic evolutionary path of ecological products from “natural gifts” to “factors of production.” The results reveal an interactive five-stage mechanism of “stipulation-unfolding-transformation-perfection-realization.” Through policy text and case analysis, we find that the relativity of concept movement is reflected in the dynamic adjustment of policy tools, while technological innovation reduces transaction costs by reconstructing property rights boundaries. This study proposes that China's practice is centered on “institutionally embedded innovation,” which localizes the natural capital paradigm through the labor theory of value. This forms a “global consensus-local innovation” dual-drive framework, providing a practical pathway for developing countries to overcome the challenges of measurement, transaction, and monetization.